(untitled) - Huenemann, Ralph William (Cambridge, Mass., 1984)
The first systematic economic analysis of China's prewar railway development ... provides significant contributions to the study of railroad economics ... includes a substantial case study in the field of 'imperialism' in which the effects of foreign investment in Chinese railroads are described and evaluated in great detail.
Keywords: Đường sắt,Railroads; Lịch sử,History; Trung Quốc,China